Using an integrative approach to assess brand identity - Barros, Teresa (2007)
There is a wide agreement that identity is a multidisciplinary concept. The authors consider this an opportunity do develop a framework to assess identity. In a marketing context, literature reveals two approaches on identity: one focus on corporate identity and the other focus on branding. The aim of this paper is to integrate these two approaches to develop a synthesis framework to assess brand identity. Based on literature on identity the authors found nine components related to brand identity. Those components are described in this paper as well as the relation they have with brand identity. The authors hope that this synthesis approach contributes to a better understanding of the brand identity, and are very encouraging for refining this framework in the future.